2019
DOI: 10.1186/s12889-019-7957-9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and their relationship to gender and depression among young adults in Iraq: a cross-sectional study

Abstract: BackgroundAdverse childhood experiences (ACEs) are considered as universal public health problem that associate with mental disorders and risky behaviors during adulthood. The aims of the paper are to estimate the prevalence of Adverse childhood experiences (ACEs) among young adults in Iraq as well as to estimate the association between ACEs and depression.MethodsA convenience sample of young adults of 18–20 years was chosen from centre and west of Iraq, mainly from universities. The adverse childhood experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…In a similar study, conducted among 401 Iraq young adults aged from 18 to 20 years, Shawi et al found a link between depression and most types of ACEs. Depression was statistically significantly correlated with emotional abuse, emotional neglect, physical abuse, and physical neglect [28]. Lemon et al in a study concerning factors linked to depressive symptoms among 666 racial and ethnic minority students of 7 diverse universities in the state of Georgia showed that Adverse Childhood Experiences were connected to more severe depressive symptoms.…”
Section: Factors Associated With Adverse Childhood Experiencesmentioning
confidence: 98%
“…In a similar study, conducted among 401 Iraq young adults aged from 18 to 20 years, Shawi et al found a link between depression and most types of ACEs. Depression was statistically significantly correlated with emotional abuse, emotional neglect, physical abuse, and physical neglect [28]. Lemon et al in a study concerning factors linked to depressive symptoms among 666 racial and ethnic minority students of 7 diverse universities in the state of Georgia showed that Adverse Childhood Experiences were connected to more severe depressive symptoms.…”
Section: Factors Associated With Adverse Childhood Experiencesmentioning
confidence: 98%
“…Four or more ACEs raised the probability of depression (4.5 times) according to a survey conducted by a big US HMO [8]. Physical and emotional neglect were reported to be the most common forms of ACEs among Iraqi young adults, both of which are linked to depression in adulthood [16]. Physical and emotional maltreatment were revealed to be the most common forms of ACEs among young adults in Iraq [16], both of which are linked to depression in adulthood.…”
Section: Ace and Depressionmentioning
confidence: 99%
“…In life course epidemiology, early life experiences are understood to be important determinants of later-life health ( Cheong et al, 2017 ; Cristóbal-Narváez et al, 2016 ; Hughes et al, 2016 , 2017 ; Nurius et al, 2012 ; Shawi et al, 2019 ; Westreich & Greenland, 2013 ), and there is a growing recognition of the influence of Adverse Childhood Experiences (ACEs). ACEs are ‘potentially traumatic events or chronic stressors that occur before the age of 18 and are uncontrollable to the child’( Felitti et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%